The National SOM Survey 1993 - SOM Institute, University of Gothenburg (University of Gothenburg, 1994)
This dataset contains information from SOM-survey 1993, the eighth study in a series of annual surveys. The questionnaire was divided into six subject fields: mass media; politics and society; energy, nuclear power and environment; Sweden and the rest of the world; leisure; and background. Many of the questions are replications of questions asked in previous SOM-surveys, but there is also a number of questions not asked in previous surveys. These questions deals with thoughts of giving up morning paper subscription; confidence in a number of Swedish mass media; impression of morning television; interest in a number of political areas; opinion on family policy; and opinion on a number of statements concerning the regional division of Sweden. The respondents also had to indicate how threatening they considered a number of environmental problem, and to give their opinion on how seriously a number of risks threaten their own life and health. Furthermore the respondents had to indicate the importance of a number of circumstances when giving refugees residence permit in Sweden, and also give their opinion on a number of statements occurring in the discussion about refugees and immigration.

Purpose:

The main purpose is to establish time series that enable researchers to analyse how various changes in society affect people's attitudes and behaviour.

Detta är den åttonde undersökningen i serien Riks-SOM, en nationell frågeundersökning med syfte att kartlägga den svenska allmänhetens vanor och attityder på temat samhälle, opinioner och medier.

1993 års undersökning består av sex sammanhållna delar: massmedier; politik och samhälle; energi, kärnkraft och miljö; Sverige och omvärlden; fritid; samt bakgrundsfrågor.

Många av frågorna har ställts i tidigare SOM-undersökning, men ett antal frågor har tillkommit. Nya frågeställningar i Riks-SOM 1993 tar upp funderingar på att upphöra med prenumeration på morgontidning; förtroende för svenska massmedier; inställning till morgon-TV; inställning till olika familjepolitiska stödformer; samt den regionala indelningen i Sverige. Respondenten fick också för ett antal miljöproblem ange hur allvarliga hot man anser dessa vara mot miljön i Sverige, och hur stora man bedömde olika risker vara för sitt eget liv och hälsa. Dessutom fick respondenten ange hur stor vikt olika omständigheter skall ha för att flyktingar skall få uppehållstillstånd i Sverige och ange sin egen inställning i ett antal påståenden om flyktingar och invandring.

Genom att frågor ställts på ett likartat sätt över tid finns det i SOM-serien tidsserier om bland annat medieanvändning, politik, kärnkraftsopinion och förtroende för olika samhällsinstitutioner och grupper.

Syfte:

Huvudsyftet är att etablera tidsserier som gör det möjligt att analysera hur olika samhällsförändringar påverkar människors attityder och beteenden.
Den nationella SOM-undersökningen 1993
Riks-SOM 1993
Keywords: elections; val; mass media; massmedia; population migration; migration; defence; försvar; participation; deltagande; public sector; offentlig sektor; international relations; internationella relationer; energy; energi; environment; miljö; leisure time; fritid; internal politics; inrikespolitik; CORS; CORS; Media; Media; Environment and conservation; Miljö och naturvård; Energy and natural resources; Energi och naturresurser; Political behaviour and attitudes; Politiska beteenden och attityder; International politics and organisations; Internationell politik och organisationer; Leisure, tourism and sport; Fritid, turism och sport; Social Sciences; Samhällsvetenskap; Political Science; Statsvetenskap; Media and Communication Studies; Medie- och kommunikationsvetenskap